2014
DOI: 10.1111/bcpt.12257
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Biology, Toxicology and Alternative Methods Development Go Hand‐in‐Hand

Abstract: Toxicological research faces the challenge of integrating knowledge from diverse fields and novel technological developments generally in the biological and medical sciences. We discuss herein the fact that the multiple facets of cancer research, including discovery related to mechanisms, treatment and diagnosis, overlap many up and coming interest areas in toxicology, including the need for improved methods and analysis tools. Common to both disciplines, in vitro and in silico methods serve as alternative inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Source: EPARs and FDA label texts, additional sources indicated where appropriate. 1 No formal studies done. 2 Food serves as gastrointestinal protection.…”
Section: Stomach Ph Regulating Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: EPARs and FDA label texts, additional sources indicated where appropriate. 1 No formal studies done. 2 Food serves as gastrointestinal protection.…”
Section: Stomach Ph Regulating Drugsmentioning
confidence: 99%
“…In the first place new agents are designed fulfilling the requirements for personalized medicine. The advancement of techniques such as (cell-based) high throughput screening and the diverse possibilities in molecular modeling have lead to a therapeutic target-based drug discovery regime [1,2]. Along with the evolution of synthetical methods, compounds are found that are highly specific and demonstrate great affinity for molecular targets [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, various modelling approaches have analysed ‘omics data sets to generate biomarker signatures or to characterize mechanisms of toxicity at a system-wide level, but suffer from the high dimensionality of omics data relative to sample number as well as problems in scaling across experimental systems (for example, hepatocyte cultures to liver) or species (for example, rat to human)111213141516. Complicating predictive biomarker discovery, different genes and gene families will unlikely have similar dose response, so dose-dependent transitions will influence the classification of (toxic) modes-of-action1718.…”
mentioning
confidence: 99%
“…The US Broad Institute Connectivity Map (CMap) data set has thousands of gene expression profiles of mostly FDA approved drugs and has been used to connect small molecules, genes and diseases (‘connectivity mapping’) to define biologically similar compounds, including for the purpose of identifying toxic modes of action11152526272829. The US National Cancer Institute (NCI) 60 tumour cell line screen includes results on GI 50 (50% growth inhibition), total growth inhibition (TGI), and LC 50 (50% lethal concentration) for many compounds tested in the major CMap cell lines30.…”
mentioning
confidence: 99%
“…Cancer research in particular, is the area where a wealth of diverse omics data are produced, and one that has introduced integration methodologies for all available information to draw a more complete view of the biological mechanisms of the disease. Along these lines, a recently published review presents a cancer research‐inspired pipeline that applies high‐throughput and high‐content profiling technologies integrated with omics profiling for assessing toxicity of chemicals and engineered nanomaterials . The authors emphasize how, in analogy to biomarker discovery in cancer research, toxicology's aim is to identify genes or pathways from the “toxome” that could predict specific toxicity effects.…”
Section: Introductionmentioning
confidence: 99%